Developing English Grammar Textbook for the Students of General English Course (GEC) at Mahesa Institute Pare - Andini Septama Sari (Language-Edu, 2019)
The study was Research and Development (R&D) in which the main purpose is to develop educational product, in this term is textbook. The researcher conducted several steps to develop an appropriate English grammar textbook. The prosedures are; (1) needs analysis and needs assessment as reference study (2) materials development (3) expert validation (4) revision (5) try out (6) final product. The data of the study were collected through the observation questionnaire, interview and expert validation checklist. Based on data of need analysis which was followed by 20 students who filled the questionnaire, students of GEC at Mahesa Institute conveyed that grammar is the most difficult material in learning English. Also, the existing textbook does not appropriate. It was because the content of the textbook was not relevant to students’ needs. To cope with this problem, the researcher developed English grammar textbook based on their need. The results of need assessment become the basis of how the researcher composed the grammar textbook. Then the findings of the study indicated that the developed material was appropriate. The product fulfills students’ need in general. The result of the tryout proves that the product makes the students more interested in English and they became more motivated in learning English grammar. Keywords:developing material, textbook, basic grammar